Revealing unusual chemical bonding in planar hyper-coordinate Ni2Ge and quasi-planar Ni2Si two-dimensional crystals - Yang, Li-Ming; Popov, Ivan A.; Frauenheim, Thomas; Boldyrev, Alexander I.; Heine, Thomas; Baciac, Vladimir; Ganz, Eric (Physical Chemistry Chemical Physics, 2015)
We discover unusual chemical bonding in a novel planar hyper-coordinate Ni2Ge free-standing 2D monolayer, and also in a nearly planar slightly buckled Ni2Si monolayer. This unusual bonding is revealed by Solid State Adaptive Natural Density Partitioning analysis. This analysis shows that a new type of 2c-2e Ni-Si σ and 3c-2e Ni-Ge-Ni σ bonds stabilize these 2D crystals. This is completely different from any previously known 2D crystals. Both of these free-standing monolayers are global minima in two-dimensional space. Although their exotic structure has unprecedented chemical bonding, they show extraordinary stability as single layers. The stabilities of these frameworks are confirmed by phonon dispersion calculations and ab initio molecular dynamics calculations. For Ni2Si, the framework was maintained during short 10 ps molecular dynamics annealing up to 1500 K, while Ni2Ge survived 10 ps runs up to 900 K. Both systems are predicted to be non-magnetic and metallic. As these new 2D crystals contain hypercoordinated Group 14 atoms, they are examples of a new class of 2D crystals with unconventional chemical bonding and potentially exciting new properties. Interestingly, we find that the stabilities of Ni2Si and Ni2Ge are much higher than that of silicene and germanene. Thus, this work provides a novel way to stabilize 2D sheets of Group 14 elements.
CRIS-Team Scopus Importer:2023-03-20